Badania kliniczne i doświadczalne w chorobach serca, płuc i naczyń Tissue engineering methods as a potential instrument used in treatment of circulatory system diseases - Wilczek, Piotr; Przybylski, Roman; Zembala, Marian (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2006)
Tissue engineering as well as the cell culture techniques seem to be the promising perspective of alternative treatment of circulatory system diseases. Quite recently, mentioned methods have been still only in the phase of in vitro tests or animal experiments. However, presently they are more often used in clinical practice. Cell transplantations or heart bioprostheses constructions based on autologous cells – are only two examples of tissue engineering usage. There are two different methods to obtain the bioprosthesis scafolds: first based on biodegradable materials usage, while the second prefers usage of biological material – acellular matrix. The cell material consists of mature somatic cells or stem cells. In a study, chosen issues regarding usage of cell therapies and cell engineering in clinical practice have been presented. Moreover, own experiences concerning preparation of biological patch using acellular pericardium covered with smooth muscule cells have been presented. Mentioned patch could be used in procedures of surgical reconstruction of left ventricle.